About a gross external debt of the Kazakhstan - Калдияров, Д. А.; Алимханова, М. М. (Journal of Economic Research & Business Administration, 2015)
Summary. In the article theoretical aspects and a ccurrent state of an external debt of Kazakhstan, its structure, and a problem of regulation and development of external loans are considered.